ANALISIS PENDAPATAN NELAYAN TANGKAP DI DESA MAFUTUTU - Datje Renjaan; Juliani Ibrahim (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2021)
The fisheries sector has an important role in National Development including creating job opportunities, increasing income and welfare for fishing communities, and support regional development. This study aime to determine how much influence the number of production costs, the number of workers and experience of the workforce on the income fisherman in mafututu sub-distrct tidore east.the study used a quantitative descriptive method withsurvey techniques. The number of samples in this study were 60 fisherman who spread over six neighborhoods in the mafututu village. The data in this study analayzed using multiple regression analysis technique whit the equation Y = α + ß1X1+ ß2X2 + ß2X2 + ß3X3 + e from the model used it is obtained regression equation Y= 4,084 + 0,0440 X1 + -0,0343 X2 + -0,0382 X3 Thus it is know that simultaneously production coasts, labor and experience at sea has a significant effect of 97,28 % on the income of fisherman, partially only variable production coast and experience at sea that has a positive and significant influence on fishermens income while the labor variable has no effect on fishermans income